PEMANFAATAN DATABASE KEPENDUDUKAN UNTUK APLIKASI E-GOV DAN SISTEM INFORMASI DI PEMKAB BANTUL - Sutanta, Edhy (BAPPEDA Kabupaten Bantul, DIY, 2012)
e-Gov is believed to be one effective way of achieving good governance, thereby triggering a lot of central government agencies and local governments to develop web applications with a view to implementing e-Gov. In fact the development of e-Gov is not easy and many have failed. The main factor of such failure is due to a misunderstanding of the concept of e-Gov and many factors. This paper reveals an idea of the use of population databases for e-Gov applications and information systems are implemented in Bantul regency, and agencies / institutions in the district of Bantul. The conclusion is the development of e-Gov strategy requires a focused and continuous short-term and long term. Framework of a consistent implementation strategy in the system life cycle is accompanied by a process of continuous improvement; availability of the technical team; leadership, institutional, and strong policies; and application of the methodology through evolution in the implementation of integration (database, midleware, and applications), are important aspects that need to be considered to support the successful implementation of e-Gov applications and systems in the Bantul regency.